KOMPLIKASI VASKULAR PASCA PROSEDUR KARDIAK DI RUANG RAWAT INTENSIF KARDIAK (ICCU/ INTENSIVE CARDIOVASCULAR CARE UNIT) - Maha Fitra ND; Wahyu Ekawati (CV. ADIBA ADISHA AMIRA, 2025)
Since the development of interventional cardiology, including coronary procedures and intracardiac implant devices, the use of arterial vessel access, particularly through the radial and femoral arteries, has become increasingly frequent. However, these transradial and transfemoral approaches have been associated with various vascular complications at the access sites particularly in ICCU. Such complications increase the risk of mortality, morbidity, healthcare costs, and the length of patient hospitalization. Early detection and prompt management of complications in ICCU are crucial to reducing post-procedural mortality and morbidity.